2020
DOI: 10.1111/jfb.14571
|View full text |Cite
|
Sign up to set email alerts
|

Red elemental selenium (Se0) improves the immunoactivities of EPC cells, crucian carp and zebrafish against spring viraemia of carp virus

Abstract: Selenium, as an essential trace element, interferes through selenoproteins in many physiological processes of plants and mammals. Its antiviral activity has recently attracted much attention because selenium improves the antiviral capacity of animal cells against a few viruses relevant to human diseases. In this study, the red elemental selenium was purified from the fermentative culture of Herbaspirillum camelliae WT00C and then used to culture epithelioma papulosum cyprinid (EPC) cells or feed crucian carp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Furthermore, the higher expression of IL-2, IL-6, and IFN-γ in the spleen which acts as a secondary lymphoid organ where the maturation and activation of B and T lymphocytes take place after glycine nano-selenium solution administration indicated improved immune response. This results were consistent the studies by Luan et al [ 59 ], Sun et al [ 60 ], and Tian et al [ 61 ] which reported that various types of selenium could improve the production of IL-1β, IL-6, and INF-γ cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the higher expression of IL-2, IL-6, and IFN-γ in the spleen which acts as a secondary lymphoid organ where the maturation and activation of B and T lymphocytes take place after glycine nano-selenium solution administration indicated improved immune response. This results were consistent the studies by Luan et al [ 59 ], Sun et al [ 60 ], and Tian et al [ 61 ] which reported that various types of selenium could improve the production of IL-1β, IL-6, and INF-γ cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Tian et al [77] purified the chemical element selenium from the fermentation of Herbaspirillum camelliae WT00C. Selenium is an essential trace element with antiviral properties.…”
Section: Medicinal Plants Against Svcvmentioning
confidence: 99%
“…The conversion of selenate into non-toxic elemental selenium or incorporation of selenium into bacterial proteins to form selenoproteins in H. camelliae WT00C facilitated selenium accumulation in tea when the bacterium colonized in tea plant [7]. Red elemental selenium (Se 0 ) purified from H. camelliae WT00C cells improved immunoactivities of crucian carp and zebrafish against spring viraemia of carp virus [45].…”
Section: Glutathione and Selenocompound Metabolismsmentioning
confidence: 99%